2017
DOI: 10.3389/fmicb.2017.00816
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Laboratory Evolution of Antibiotic Resistance Using Different Selection Regimes Lead to Similar Phenotypes and Genotypes

Abstract: Antibiotic resistance is a global threat to human health, wherefore it is crucial to study the mechanisms of antibiotic resistance as well as its emergence and dissemination. One way to analyze the acquisition of de novo mutations conferring antibiotic resistance is adaptive laboratory evolution. However, various evolution methods exist that utilize different population sizes, selection strengths, and bottlenecks. While evolution in increasing drug gradients guarantees high-level antibiotic resistance promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 81 publications
5
75
0
Order By: Relevance
“…Mutations in fusA1 were found in several different species including E. coli , S. typhimurium , and S. aureus (Ibacache-Quiroga et al, 2018; Jahn et al, 2017; Johanson and Hughes, 1994; Kim et al, 2014; Mogre et al, 2014; Norström et al, 2007), and all laboratory studies reported these mutations either in response to aminoglycoside selection or as a direct cause of aminoglycoside resistance (Figure 4). Mutations in cyoA and cyoB were also found in E. coli and S. typhimurium in these experiments (Ibacache-Quiroga et al, 2018; Jahn et al, 2017; Johanson and Hughes, 1994). Multiple sequence alignment of these genes across species revealed that fusA1 mutations were localized to two primary regions across all species and were primarily nonsynonymous SNPs, and eight positions exhibit amino acid-level parallelism across species (Figure 4, Table S1, Figure S5) (Wattam et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in fusA1 were found in several different species including E. coli , S. typhimurium , and S. aureus (Ibacache-Quiroga et al, 2018; Jahn et al, 2017; Johanson and Hughes, 1994; Kim et al, 2014; Mogre et al, 2014; Norström et al, 2007), and all laboratory studies reported these mutations either in response to aminoglycoside selection or as a direct cause of aminoglycoside resistance (Figure 4). Mutations in cyoA and cyoB were also found in E. coli and S. typhimurium in these experiments (Ibacache-Quiroga et al, 2018; Jahn et al, 2017; Johanson and Hughes, 1994). Multiple sequence alignment of these genes across species revealed that fusA1 mutations were localized to two primary regions across all species and were primarily nonsynonymous SNPs, and eight positions exhibit amino acid-level parallelism across species (Figure 4, Table S1, Figure S5) (Wattam et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The Amk3 mutant had point mutations in nuoH, cpxR, crr, fusA, and rffG, as well as a small deletion in lrhA. While the effect of crr, rffG, and lrhA mutations are not clear, the fusA, cpxR, and nuoH mutations are often associated with resistance towards aminoglycosides 18,19,23 . The nuo genes encode subunits of NADH:quinone oxidoreductase I, which maintains the PMF to fuel respiration 24 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to promoting antibiotic resistance development in circulating strains, epistatic interactions between resistance determinants may also lead to increased resistance or collateral sensitivity during sequential treatment regimes in individual patients [15][16][17][18] . For example, mutations associated with aminoglycoside resistance confer sensitivity towards multiple antibiotic drug classes, including beta-lactams, quinolones, and tetracyclines [17][18][19] , and this sensitivity is thought to arise from a reduction in the proton motive force (PMF) that reduces the uptake of aminoglycoside, while simultaneously decreasing multidrug efflux 18 .…”
mentioning
confidence: 99%
“…Experimental evolution of antibiotic-resistant mutants from sensitive parent strains, followed by whole genome sequencing to identify resistance-conferring mutations, is an approach that has been applied to a number of species (16)(17)(18)(19)(20)(21), including P. aeruginosa (22)(23)(24)(25)(26)(27)(28). Studies have confirmed the involvement of genes previously proposed to be associated with resistance in P. aeruginosa.…”
Section: Introductionmentioning
confidence: 88%